Ed's Basic Histology Gallery (Out of Print) - Edward Friedlander (Association of American Medical Colleges, 2007)
Abstract This resource is an interactive website that introduces all the essential elements of human tissue. After reading a short text, visitors working singly or together to identify the photographs. The website introduces basic concepts of histology actively, without users or teachers having to schedule classroom time. Anyone planning a career in medicine or bioscience will need basic histology competency in the years ahead. Those becoming doctors will need it to make sense of what is happening at the tissue level-in pathology, in reading professional journals, and when caring for sick people. Those attending the Kansas City University of Medicine and Biosciences (KCUMB) will need it to complete their three pathology signoffs and hundred-or-so lab cases successfully. Doctors, regardless of their specialty, will be expected to review at least some of their own biopsies with a pathologist. Laypersons can use the site to help themselves understand popular articles about medical science, especially those with schematic drawings of tissues. KCUMB Students who complete this exercise can expect to be successful on the first histology signoff. (It is considered a requirement for completing the first unit of the new curriculum.) In this exercise, learners are required to identify, all by themselves, under a real microscope, in the company of a flesh-and-blood instructor, each of the following: nuclei, euchromatin and heterochromatin, nucleoli, mitotic figures, cytoplasm, simple columnar/cuboidal epithelium, stratified squamous epithelium, exocrine glands, smooth muscle, skeletal muscle, collagen fibers, fat, blood vessels, lymphatic vessels, red blood cells, neutrophils, and lymphocytes. Unlike a classic histology microscope lab, users receive immediate feedback. This may help reduce the need for scheduling classroom and/or lab time.